Moderators of the relationship between social bonding and organizational commitment. Issue 3 (6th May 2014) - Shih-Tse Wang, Edward
Abstract : Purpose: – The commitment of service employees to an organization is a critical concern that affects the success of an organization. The purpose of this paper is to investigate whether the social bonds between the supervisor and the employee, and among employees, foster organizational commitment in employees. The study subsequently explored the moderating role of work status (full-time vs parttime) and employee individualistic values in the relationship between social bonding and commitment. Design/methodology/approach: – Empirical data were collected from the frontline employees of restaurants in Taiwan ( n =395). Hierarchical moderated regression analysis was used to examine the relationship between social bonds and relationship commitment and the moderating effect of work status and individualistic values on the social bonding-commitment relationship. Findings: – The results show that social bonding is an antecedent to organizational commitment, and work status and individualistic values moderate the social bonding-commitment relationship. The effect of social bonding on organizational commitment is stronger for full-time and less individualistic employees than for part-time and more individualistic employees. Originality/value: – This research contributes to knowledge of the effect of social bonding on employee organizational commitment, and provides evidence showing that work status and employee values affect the social bonding-commitment relationship.